Anti-inflammatory activities of astringent persimmons (Diospyros kaki Thunb.) stalks of various cultivar types based on the stages of maturity in the Gyeongnam province - Jieun Choi; Mi Jeong Kim; Richard Komakech; Haiyoung Jung; Youngmin Kang (BMC, 2019)
Abstract Background Natural products play a significant role in human health in relation to the prevention and treatment of inflammatory conditions. One of the plants with great medicinal potentials is Diospyros kaki which is mainly cultivated in Asian countries including Korea, Japan, and China. Astringent D. kaki is a wild species with an astringent taste until they are Ripened. kaki calyx is a traditional Korean medicine (TKM) made from the stalks of astringent D. kaki and is used in treating bed-wetting, vomiting, and hiccupping. The present study was designed to investigate the potential anti-inflammatory activities of astringent D. kaki stalks based on cultivar types and stages of maturity. Methods The anti-inflammatory effects of the stalk extracts of local astringent D. kaki cultivar species were evaluated on RAW 264.7 cells. Cell viability was measured using a Cell Counting Kit-8 (CCK8) method. The anti-inflammatory effects were determined by measuring the nitric oxide (NO) concentration of the supernatant. Cellular signaling pathways were determined by quantitative polymerase chain reactions of inducible nitric oxide synthase (iNOS). Protein expression of iNOS and phospho-p65 was determined using western blot, and the nuclear localization of p65 was determined using confocal imaging in RAW 264.7 cells. Results We found that the stage 1 (8-9 month) samples all showed a high percentage of tannic acid content and Gojongsi (Hamyang) stalks had the highest content. The stage 1 samples also showed the highest inhibition of NO production. Decreases in the expression of iNOS and phosphorylated p65, and in the nuclear localization of p65, were dose-dependent. All the extracts were nontoxic under 100 μg/ml concentration. Conclusion This study provides insight into the changes in tannic acid content in astringent D. kaki and their anti-inflammatory effects, in relation to their stage of maturity. These results are expected to be useful in the verification of the efficacy of oriental medicine and the timing of proper harvest for medical use.